Enhanced plasma protein carbonylation in patients with myelodysplastic syndromes - Hlaváčková, Alžběta; Štikarová, Jana; Pimková, Kristýna; Chrastinová, Leona; Májek, Pavel; Kotlín, Roman; Čermák, Jaroslav; Suttnar, Jiří; Dyr, Jan Evangelista (Free radical biology & medicine, 2017)
Myelodysplastic syndromes (MDS) represent a heterogeneous group of pre-leukemic disorders, characterized by ineffective hematopoiesis and the abnormal blood cell development of one or more lineages. Oxidative stress, as an important factor in the carcinogenesis of onco-hematological diseases, is also one of the known factors involved in the pathogenesis of MDS. An increase of reactive oxygen species (ROS) may lead to the oxidation of DNA, lipids, and proteins, thereby causing cell damage. Protein carbonylation caused by ROS is defined as an irreversible post-translational oxidative modification of amino acid side chains, and could play an important role in signaling processes. The detection of protein carbonyl groups is a specific useful marker of oxidative stress. In this study, we examined 32 patients divided into three different subtypes of MDS according to the World Health Organization (WHO) classification criteria as refractory anemia with ringed sideroblasts (RARS), refractory cytopenia with multilineage dysplasia (RCMD), refractory anemia with excess blasts-1,2 (RAEB-1,2). We found significant differences in protein carbonylation between the group of all MDS patients and healthy controls (P=0.0078). Furthermore, carbonylated protein levels were significantly elevated in RARS patients compared to healthy donors (P=0.0013) and to RCMD patients (P=0.0277). We also found a significant difference in the total iron binding capacity (TIBC) between individual subgroups of MDS patients (P=0.0263). Moreover, TIBC was decreased in RARS patients compared to RCMD patients (P=0.0203). TIBC moderately negatively correlated with carbonyl levels (r=-0.5978, P=0.0054) in the MDS patients as a whole. Additionally we observed changes in the carbonylated proteins of RARS patients in comparison with healthy controls and their negative controls. Using tandem mass spectrometry (LC-MS/MS) we identified 27 uniquely carbonylated proteins of RARS patients, which were generated by ROS and could influence the pathophysiology of low-risk MDS. These data indicate that increased protein carbonylation is related with RARS as low-risk MDS subgroup. We suggest that this type of post-translational modification in MDS disease is not "only" a consequence of oxidative stress, but also plays an active role in the pathophysiology and iron metabolism within the RARS subgroup of MDS. Measurement of plasma carbonyl levels and the isolation of carbonylated plasma proteins, followed by their identification, could serve as a potential diagnostic and prognostic tool in MDS.
Keywords: senioři; Protein Binding; Carbonylated proteins; karbonylace proteinů; krevní proteiny; Prognosis; reaktivní formy kyslíku; Anemia, Refractory; Blood Proteins; Middle Aged; Myelodysplastic Syndromes; mužské pohlaví; Oxidative Stress; železo; Adult; mladý dospělý; refrakterní anemie; myelodysplastické syndromy; Reactive Oxygen Species; Iron; Young Adult; ženské pohlaví; prognóza; Myelodysplastic syndromes; Humans; Tandem Mass Spectrometry; Carbonyl levels; Oxidative stress; vazba proteinů; lidé středního věku; Protein Carbonylation; tandemová hmotnostní spektrometrie; dospělí; oxidační stres; Female; Aged; lidé; Male